Economics of public policy : the micro view - Goodman, John C.; Dolan, Edwin G. (St. Paul : West Publishing Company, 1982)
The primary purpose of this book is to help students understand how economic theory applies to the real world. It does this by showing how some of the most important public policies reflect economic principles in action. It also shows how economics relates to other disciplines as well- History, Sociology, Political Science, and even ethics.
Includes bibliographical references.
ne 21/06/2018
Loans
Keywords: Policy sciences; Economic policy